EFFECT OF SEED EXTRACT JUWET (Eugenia JAMBOLANA) DECREASE OF BLOOD GLUCOSE CONCENTRATION IN MICE BALB / c MALE THAT INDUCIBLE STREPTOZOTOCIN - Inawati Inawati (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2010)
Acording to the data in the journal of Diabetes Care 2004, DM patient in Indonesia in 2000 reach 8,4 million people. And ranked 4th after India, Cina and USA. Population will increase more than two times in 2030, reach 21,3 million people. This study was to prove effect of extract juwet seed in blood glucose level in mice after induction of Streptozotocin (STZ). This was experimental study using white male BALB/c strain mice, 10 weeks old with bodyweight of 25-35 grams. Group 1 was received no STZ and extract juwet seed sacrified in 3th day. Group 2 was received STZ but no extract juwet seed , sacrified in 3th day. Group 3 was received STZ but no extract juwet seed, sacrified in 18 th day. Group 4 was received STZ and received extract juwet seed. Group 5 was received no STZ and extract juwet seed, sacrified in18th day. Fasting blood glucose and 2 hours after given oral glucose was examined in 3th day and in 18th day.  There was significant difference between group those received STZ and received no extract juwet seed and those that received STZ but received no extract juwet seed in the result of Anova analyzed for fasting blood glucose level (p<0,05) and Anova analyzed showed significant difference (p<0,05) between blood glucose level 2 hours after given glucose who received STZ but received no extract juwet seed and those who received STZ and received extract juwet seed. The conclusion of this experiment was the level of fasting blood glucose and level blood glucose 2 hour s after given glucose of mice who received STZ and received no extract juwet seed less than in mice who received STZ and received extract juwet seed.